There’s huaca in the back: Heritage values from different communities. The case of San Borja huaca - Moreno Ortiz, Franco (2025)
The San Borja Huaca is in a very distinctive context: at the border of the district of San Borja, at the border of a slum opposed a housing complex, and at the back of large-scale buildings such as the Ministry of Culture. Despite seemingly having concluded the value enhancement process, the San Borja Huaca remains closed to the public with no admission for visitors. The combination of circumstances of the minimal attention to the Huaca by the authorities added to the isolation between both communities provides a disadvantageous scenario for the bonding towards the Huaca, but this does not imply that the bonding could not happen. This research aims to provide an overview of the present, using qualitative metrics to recognize heritage values held by all the social stakeholders associated with the San Borja Huaca, emphasizing on the social stakeholders who should be most capable of enjoying the Huaca: the residents. Through this study, it will be possible to validate whether these social actors have a connection to the San Borja Huaca, serving as a foundation for understanding these connections and guiding future interventions.